"You Look at an Ocean; I See the Rips, Hear the Waves, and Feel the Currents": Dwelling and the Growth of Enskiled Inhabitant Knowledge. Issue 3 (2nd October 2021) - Woods, Carl T.; Davids, Keith
Abstract: This inquiry explores a theoretical question, of applied practical relevance in fields like sport science, relating to how people come to know the performance landscapes they inhabit, and the dynamic opportunities for action they present. Here, we propose that how people come to know their performance landscapes, and how they learn to correspond with available affordances in them, is through dwelling. More specifically, through dwelling, people learn to resonate with the rhythms of information and affordances of a performance landscape, entangling with them to successfully find their way through the tasks, problems and challenges taken up with. To theoretically support our analysis, we draw on James Gibson's different conceptualisations of knowledge, and Tim Ingold's perspectives of enskilment – bringing practical applicability to our discussion by weaving in various ethnographic accounts of the growth of enskiled inhabitant knowledge . Through these transdisciplinary insights, we show that it is by asking questions, sharing stories, and following up lines of inquiry that people grow into their enskiled knowledge of places they inhabit.